Persepsi Siswa terhadap Keterampilan Berkomunikasi Guru dalam Pembelajaran di SMK Negeri 9 Padang - Arsela, Maria; Syahril, Syahril (Lembaga Yasin AlSys, 2023)
This research is based on the results of observations made by the author during observations at SMK N 9 Padang, from the observations made it appears that there are still teachers who have poor communication skills in learning. This research aims to obtain data and information regarding how good the communication skills of teachers at SMK N 9 Padang are in learning according to students' perceptions seen from several aspects: 1) conveying messages orally, 2) conveying messages in writing, and 3) receiving messages. Therefore, the problem that will be studied in this research is,